Thermoplastic vulcanizates derived from modified natural rubbers and polypropylene - Laksana Saengdee (2022)
A thermoplastic vulcanizate (TPV) with improved mechanical properties and recyclability was developed from modified natural rubber (NR) and polypropylene (PP). The modified NRs were prepared through two modification steps, i.e., epoxidation (E) and followed by hydrogenation (H). In addition, two levels of modification were prepared, i.e., one with 17% E and 27% H (HENR-1) and the other 28% E and 25% H (HENR-2). These modified NRs were compounded with vulcanizing agents before subjecting to dynamic vulcanization of the modified NR/PP in an internal mixer. The rubber to PP ratio was fixed at 70:30. Morphological study using scanning electron microscopy showed agglomerations of dispersed vulcanized rubber particles in continuous PP phase. It has been found that TPV of HENR-2/PP exhibits outstanding mechanical properties of tensile strength at 7.84 MPa and elongation-at-break at 171.43%. In addition, the elongation-at-break of HENR-2/PP was further increased when 3 phr of polypropylene-grafted-maleic anhydride (PP-g-MA) was introduced, which might be due to the interaction of MA in PP-g-MA with the epoxide unit of HENR. Reprocessing of HENR/PP TPV showed that the developed TPVs could be reprocessed several times. The obtained results suggest that these HENR/TPVs could offer an alternative way for the utilization and sustainability of NR. Graphical abstract: [Figure not available: see fulltext.].